Elderly and Nonelderly Use of a Dedicated Ambulance Corps' Emergency Medical Services in Taiwan. (11th July 2016) - Huang, Chien-Chia; Chen, Wei-Lung; Hsu, Chien-Chin; Lin, Hung-Jung; Su, Shih-Bin; Guo, How-Ran; Huang, Chien-Cheng; Chen, Pi-Ching
Abstract : Backgrounds and Aim . Taiwan's population is gradually aging; however, there are no comparative data on emergency medical services (EMS) use between the elderly and nonelderly. Methods . We analyzed the emergency calls dealt with between January 1 and April 4, 2014, by EMS in one city in Taiwan. All calls were divided into two groups: elderly (≥65 years) and nonelderly (<65 years). Nontransport and transport calls were compared between the groups for demographic characteristics, transport time, reasons for calling EMS, vital signs, and emergency management. Results . There were 1, 001 EMS calls: 226 nontransport and 775 transport calls. The elderly accounted for significantly (P < 0.05 ) fewer (28 (9.2%)) nontransport calls than did the nonelderly (136 (21.4%)). In the transport calls, 276 (35.6%) were the elderly. The elderly had a higher proportion of histories for cardiovascular disease, cerebrovascular disease, hypertension, diabetes, end-stage renal disease, cancer, Parkinson's disease, and Alzheimer's disease. In addition, the elderly had significantly longer total transport time, more nontrauma reasons, and poorer consciousness levels and lower oxygen saturation and needed more respiratory management and more frequent resuscitation during transport than did the nonelderly. Conclusion . The elderly have more specific needs than do the nonelderly. Adapting EMS training, operations, and government policies to aging societies is mandatory and should begin now.